BUILDING 21st-CENTURY SKILLS WITH STEAM-PjBL - Suryaningsih, Siti; Agung, Salamah; Barke, Hans-Dieter; Nisa, Fakhira Ainun (EDUSAINS, 2024)
During the 21st century, students are encouraged to develop skills that enable them to deal with real-life problems. The purpose of this study is to analyze what kind of 21st-century skills can be built during a teaching and learning process in the classroom. Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach through a project-based learning (PjBL), or STEAM-PjBL-based learning, seems to provide a promise in the development of 21st-century skills of students. This study, therefore, is conducted to reveal the kind of skills that can be built during the STEAM-PjBL learning process. Using a literature review, this study collects and analyzes relevant articles from national and international journals through several search engine systems, such as Taylor & Francis Online, Springer, etc., and indexed databases, such as SCOPUS, DOAC, and Eric, both from the period of 2014-2022. This study found that the 4Cs of the 21st-century skills, namely, critical thinking and problem solving, communication, collaboration, and creative thinking, can be built from the activities in each stage of the STEAM-PjBL learning process.  While the skills are evident from the literature review, a further empirical study is encouraged to be conducted to ensure how the skills can be successfully developed and further improved